The screening and management of pituitary dysfunction following traumatic brain injury in adults: British Neurotrauma Group guidance. Issue 11 (31st August 2017) - Tan, Chin Lik; Alavi, Seyed Alireza; Baldeweg, Stephanie E; Belli, Antonio; Carson, Alan; Feeney, Claire; Goldstone, Anthony P; Greenwood, Richard; Menon, David K; Simpson, Helen L; Toogood, Andrew A; Gurnell, Mark; et al.
Abstract : Pituitary dysfunction is a recognised, but potentially underdiagnosed complication of traumatic brain injury (TBI). Post-traumatic hypopituitarism (PTHP) can have major consequences for patients physically, psychologically, emotionally and socially, leading to reduced quality of life, depression and poor rehabilitation outcome. However, studies on the incidence of PTHP have yielded highly variable findings. The risk factors and pathophysiology of this condition are also not yet fully understood. There is currently no national consensus for the screening and detection of PTHP in patients with TBI, with practice likely varying significantly between centres. In view of this, a guidance development group consisting of expert clinicians involved in the care of patients with TBI, including neurosurgeons, neurologists, neurointensivists and endocrinologists, was convened to formulate national guidance with the aim of facilitating consistency and uniformity in the care of patients with TBI, and ensuring timely detection or exclusion of PTHP where appropriate. This article summarises the current literature on PTHP, and sets out guidance for the screening and management of pituitary dysfunction in adult patients with TBI. It is hoped that future research will lead to more definitive recommendations in the form of guidelines.